PERAN OPPORTUNITY ENTREPRENEUR DALAM PERTUMBUHAN EKONOMI - Kurniasari, Dian (STIE Totalwin Semarang, 2013)
Not all entrepreneurs demonstrate the same kind of behaviors. An âopportunityâ entrepreneur starts a new business by exploiting an identifiable business opportunity and is expected to help develop the economy. On the other hand, a ânecessityâ entrepreneur does so in order to survive over poverty and/or unemployment, and thus can hardly contribute much to the economic development. This paper to describes this types of entrepreneur.